Experiences of black adolescents who chose to terminate their pregnancies - Winnie Seipati Mpshe; Antoinette Gmeiner; Sandra van Wyk (AOSIS, 2002)
The "Choice on Termination of Pregnancy Act" (No. 92 of 1996) determines that a woman, including a 12-year old pregnant adolescent, can choose to terminate a pregnancy without the consent of parents, guardian or friends. Opsomming Die "Wet op Keuse van Terminasie van Swangerskap" (No. 92 van 1996) bepaal dat 'n vrou, insluitend 'n 12-jarige swanger addolesent, kan kies om haar swangerskap te bemdig sonder haar ouers, voog of vriende se goedkeuring. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.